Does muscle invasive bladder cancer following pelvic radiotherapy portend worse prognosis? A seer-based study. (2020) - Natale, Caleb; Leinwand, Gabriel; Zeineddine, Farid; Silberstein, Jonathan L; Krane, Louis S
Abstract: Background: Although emerging evidence demonstrates increased risk of secondary bladder cancer following pelvic radiotherapy, the aggressiveness of these tumors is not well-characterized. Materials and Methods: A search of the Surveillance, Epidemiology, and End Results (SEER) 18 Database, identified 25, 734 patients diagnosed with bladder cancer following definitive therapy for previous pelvic malignancy. Kaplan-Meier curve analyses were utilized to determine overall survival with significance set at p<0.05. Results: Of the 25, 734 patients, 11, 376 (44.2%) received radiation treatment for their first cancer. Overall survival of bladder cancer was found to be 80%, 69.5%, and 49.2% at 1, 2 and 5 years, respectively. There was no significant survival difference between groups whose first cancer was treated with or without radiation (p=0.8). A survival advantage was seen for the bladder cancer patients not treated with radiation for cervical (p=0.004), uterine (p=0.0006), and vaginal cancers (p<0.0001). Bladder cancer patients treated with radiation for prostate cancer showed a survival advantage (p=0.002). The average time to second cancer diagnosis was 6.5±6.1 years. Patients treated with radiation for first primary cancer showed a longer time to second cancer (7.2±6.0 years) compared to those treated without radiation (5.9±6.0 years) (p<0.01). Conclusion: Patients with prior history of female cancers treated without radiation demonstrated significant survival advantage in second primary bladder cancer. A small significant survival advantage was seen in bladder cancer patients previously treated for prostate cancer with radiation. This data suggests that second primary bladder cancer following pelvic radiotherapy has similar biologic aggressiveness to urothelial carcinoma developing without a history of radiotherapy. Microabstract: The overall survival of 25, 734 patients diagnosed with bladder cancer following definitive therapy for a previous pelvic malignancy was 49.2% at 5 years. There was no significant survival difference between groups whose first cancer was treated with or without radiation. Second primary bladder cancer following pelvic radiotherapy has similar biologic aggressiveness to urothelial carcinoma developing without a history of radiotherapy.